Hyperinsulinemia-induced microglial mitochondrial dynamic and metabolic alterations lead to neuroinflammation in vivo and in vitro - Yang, Xiaohan; Xu, Yuan; Gao, Wenting; Wang, Li; Zhao, Xinnan; Liu, Gang; Fan, Kai; Liu, Shuang; Hao, Huimin; Qu, Siyan; Dong, Renhou; Ma, Xiaokai; et al. (Frontiers in Neuroscience, 2022)
Numerous studies have demonstrated that type 2 diabetes (T2D) is closely linked to the occurrence of Alzheimer’s disease (AD). Nevertheless, the underlying mechanisms for this association are still unknown. Insulin resistance (IR) hallmarked by hyperinsulinemia, as the earliest and longest-lasting pathological change in T2D, might play an important role in AD. Since hyperinsulinemia has an independent contribution to related disease progressions by promoting inflammation in the peripheral system, we hypothesized that hyperinsulinemia might have an effect on microglia which plays a crucial role in neuroinflammation of AD. In the present study, we fed 4-week-old male C57BL/6 mice with a high-fat diet (HFD) for 12 weeks to establish IR model, and the mice treated with standard diet (SD) were used as control. HFD led to obesity in mice with obvious glucose and lipid metabolism disorder, the higher insulin levels in both plasma and cerebrospinal fluid, and aberrant insulin signaling pathway in the whole brain. Meanwhile, IR mice appeared impairments of spatial learning and memory accompanied by neuroinflammation which was characterized by activated microglia and upregulated expression of pro-inflammatory factors in different brain regions. To clarify whether insulin contributes to microglial activation, we treated primary cultured microglia and BV2 cell lines with insulin in vitro to mimic hyperinsulinemia. We found that hyperinsulinemia not only increased microglial proliferation and promoted M1 polarization by enhancing the production of pro-inflammatory factors, but also impaired membrane translocation of glucose transporter 4 (GLUT4) serving as the insulin-responding glucose transporter in the processes of glucose up-taking, reduced ATP production and increased mitochondrial fission. Our study provides new perspectives and evidence for the mechanism underlying the association between T2D and AD.